Advances in Crop Breeding Through Precision Genome Editing - Nerkar, Gauri; Devarumath, Suman; Purankar, Madhavi; Kumar, Atul; Valarmathi, R.; Devarumath, Rachayya; Appunu, C. (Frontiers in Genetics, 2022)
The global climate changes and the unfavorable abiotic and biotic factors are limiting the agricultural productivity and therefore intensifying the challenges for the crop scientists to meet the rising demand for global food supply. The introduction of applied genetics to agriculture through plant breeding facilitated the development of hybrid varieties with improved crop productivity. However, the development of new varieties with the existing gene pools poses a challenge for the crop breeders. Genetic engineering holds the potential of broadening genetic diversity by the introduction of new genes in the crops. But the random insertion of foreign DNA into the plant nuclear genome often leads to transgene silencing. Recent advances in the field of plant breeding include the development of a new breeding technique called Genome editing. Genome editing technologies have emerged as powerful tools to precisely modify the crop genomes at specific sites in the genome which has been the longstanding goal of plant breeders. The precise modification of the target genome, absence of foreign DNA in the genome-edited plants, faster and cheaper method of genome modification are the remarkable features of the genome-editing technology which has resulted in its widespread application in crop breeding in less than a decade. This review focuses on the advances in crop breeding through precision genome editing. This review includes an overview of the different breeding approaches for crop improvement; genome editing tools and approaches used for crop improvement; agronomic traits such as disease resistance, abiotic stress tolerance, herbicide tolerance, yield, and quality improvement, reduction of anti-nutrients, improved shelf life and an update on the regulatory approval of the genome-edited crops.